Distributive Justice Sharing System on Sharia Based Micro Finance Institutions (Empirical Study of BMT X in Semarang) - Lasmiatun . (Jurnal Iqtisad, 2016)
AbstractBMT X is closer to the distributive justice "The principle of fair equality of opportunity", the First; Justice Depositary: For the results of the paid-up member of the BMT financing obtained in accordance with the number of the income or gains on the month, divided in accordance with its portion, Second; Storage and BMT justice: For the results received by members of the depositary in accordance with the results accepted by BMT, from members of financing in the portion or ratio multiply by agreement between BMT and members keeper, Third; despite the fine provisions enacted but is flexible according to the ability of members and funds channeled kebaitul maal, Fourth;  BMT X more synergy activities are better able to be brought closer to the economically disadvantaged even sociological, helping each other, give and take, and mutual benefit. Fifth; Trust and supervision between members and BMT X can be increased revenues members who do not always have to reduce the growth of business incomeKeywords: BMT, Member, Sharing, Justice, Revenue. مخلص البحث                         : خزينة المال الشرعية هو أقرب إلى العدالة التوزيعية "مبدأ المساواة العادلة للفرصة" (مبدأ المساواة في المعرض فرصة)، الأول العدل الوديع: لنتائج أعضاء المدفوع من التمويل ل خزينة المال الشرعيةوفقا لكمية حصل في الدخل أو المكاسب في الشهر، تنقسم وفقا لحصتها، وهما الوديع العدل و خزينة المال الشرعية: لالنتائج وفقا لأعضاء الوديع الواردة وفقا للنتائج مقبولة من قبلخزينة المال الشرعية ، التمويل عضوا ضرب من قبل جزء أو نسبة الاتفاق بينوأعضاء حارس، شروط الثالثة من الغرامات على الرغم من سريان ولكن مرنة وفقا لقدرة الأعضاء والأموال المقدمة للمال تصبح مقرا، الرابع آخر خزينة المال الشرعيةمزيد من التآزر التي يتم اقتصاديا أن يقدموا أكثر أقرب للمحرومين حتى السوسيولوجية، مما يساعد، الأخذ والعطاء، يمكن أن تكون مفيدة للطرفين، والثقة الخامس والإشراف بين الأعضاء و خزينة المال الشرعيةيمكن أن تكون زيادة أعضاء إيرادات الذين ليس لديهم دائما للحد من نمو الإيرادات التجارية.كلمات البحث:الألفاظ الأساسياة :خزينة المال الشرعية ، عضو ، مشاركة الأرباح, والعدل, والإيرادات